An investigation into how gender roles influence decision making process in the construction industry of Zimbabwe. a case of Buddington builders. - Mpapa, Patient (Midlands State University, 2017)
Market segmentation has been traditionally done based on gender considerations. Some products have been thought to target women while others are thought to be suitable for males due to gender roles .For instance automobiles have been previously targeted towards males assuming that the males would be deciders and influencers in the decision to buy. This research was aimed at investigating how gender roles influence the decision making of construction material. The objectives of the study were to establish how gender attitudes influence information search, to establish the impact of preferences on evaluation and selection, to describe how gender involvement affects purchase and to explore the influence of social relationships on post purchase behaviour The researcher used exploratory and descriptive research designs to collect data for the study from a sample of 122 customers and 19 employees. Research instruments which were used include questionnaires ,interviews as well as observations .Questionnaires were given to customers and employees to indicate and describe how male and female customers are involved in the decision making process while interviews were done with management to explore their views on whether they perceive targeting females as a worthwhile strategy. Secondary data was also considered in the study such as Company reports and sales records. Literature from journals ,text books and internet sources were also consulted to see what other scholars were putting forward in relation to gender roles and the decision making process. Data gathered indicated that gender roles influence each stage of the decision making process. The findings show that males and females look for information from different sources, have different preferences when evaluating construction material suppliers, show different levels of involvement in purchase decisions and show different post purchase behaviours because they value relationships differently. The researcher therefore recommended Buddington Builders to refurbish its retail atmosphere, recruit more female sales staff, train sales force to be friendly and patient to customers and to advertise on social network sites so as to appeal effectively to the female customer.